HYGIENE, ECOLOGY AND HUMAN HEALTH - Khazhimatov Ravshanbek Sobirzhanovich (Web of Journals Publishing, 2024)
This article contains theoretical knowledge about human hygiene and ecology and their impact on his health. The article also contains important information about human hygiene and ecology as separate areas of science and reflects the patterns of influence of environmental factors on public health. Various methods of hygienic examinations are disclosed and outlined. The article outlines the ways of sanitary education of the population. The relationship between ecology and hygiene and the foundations of environmental knowledge in preventive medicine are reflected. The environmental and hygienic importance of healthy nutrition is explained, the problems and tasks of health education of the population and the prevention of socially significant diseases are outlined. The article focuses on the sanitary and epidemiological well-being of the population and eliminating the influence of harmful factors on public health.
Keywords: hygiene, human health, habitat, sanitary and epidemiological safety of the population, the influence of environmental factors on the human body, hygienic examination methods, personal hygiene, preventive measures, health measures.